The Association of Organizational Commitment and Personal Factor With Burnout Syndrome and Turnover Intention in Nurses - Nursalam Nursalam; Shintia Ekawati; Andri Setiya Wahyudi (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2020)
Introduction: Turnover intention has many negative impacts on hospitals. The purpose of this research was to analyze the relationship between organizational commitment, personal factors and burnout syndrome to turnover intention in nurses. Methods: A descriptive analytic with cross-sectional approach, the sample was 83 nurses in type C hospital in Lamongan based on a cluster random sampling. The variables were organizational commitment, personal factor, burnout syndrome and turnover intention. Organizational commitment was measured with a modified questionnaire from Meyer and Allan, personal factors measured using demographic questionnaire, Maslach Burnout Inventory for burnout syndrome and modified questionnaire from Chen and Francesco for turnover intention. Moreover, the analysis uses ordinal regression statistical and logistic regression. Results: The results showed that the commitment factor continuance (p = 0.001), normative commitment (p = 0.000), education (p = 0.024), emotional fatigue (p = 0.008) and attitude (p = 0.008) had a significant relationship with burnout syndrome. Emotional exhaustion has significant relationship with turnover intention after adjusted with depersonalization and self-achievement (p = 0.008). Conclusion: It can be concluded that nurses in the Type C hospital can be loyal to reduce the turnover number, and this can increase the health levels of Indonesian people.